Patients Reported Outcomes (PROMS) in Hallux Valgus and Rigidus Surgery, Is There Any Difference?. Issue 4 (16th October 2019) - Alkhreisat, Mohammad; Nicolas, Andrea Pujol; Ramaskandhan, Jayasree Ramas; Mousa, Adham; Qasim, Sultan; Siddique, Malik
Category: Bunion Introduction/Purpose: There is paucity of literature comparing foot and general health status including quality of life between patients presenting with Hallux Valgus and Hallux Rigidus and to compare the outcomes of people how had surgery in either one. We compared foot specific patient reported disability and general health status between patients presenting with Hallux Valgus and Hallux Rigidus pre and post-surgery. Methods: All patients operated between June 2016 and December 2017 with a diagnosis of primary Hallux Valgus or Hallux Rigidus were invited to the study. Patients were grouped based on diagnosis into Group A (Hallux Valgus) and Group B (Hallux Rigidus). All patients received a Pre-Operative and post-operative questionnaire with a minimum of 6 months follow up. Differences were studied between groups for scores of MOX-FQ, EQ-5D (UK) and Foot and Ankle outcomes scores (FAOS) comparing both pre and post-operative. Results: There were 53 patients with Hallux Valgus and 46 patients with Hallux Rigidus of 1st MTPJ. Pre-operatively in MOX-FQ both groups reported similar level of pain (p=0.776), difficulty with walking/ standing (p= 0.960) and restriction with social activity because of foot symptoms (p=0.683). Following surgery both groups significantly improved in all domains (p< 0.001). Post- operatively there was no difference between both groups for MOX-FQ (pain, walking, social domains; p>0.05), EQ-5D general health score (p=0.404) and FAOS domains for pain (p=0.653), symptoms (p=0.230), ADL (p=0.587), and quality of life (p=0.876). But all scores improved significantly from pre-op to post-op for both groups (p<0.001). Conclusion: There is no difference in foot related quality of life, general health status and higher functional disability levels between patients presenting with Hallux Valgus vs. Hallux Rigidus before surgical intervention. The impact of these conditions on disability levels remain the same, amidst the difference in pathology. Surgery for both pathologies equally improves foot related quality of life and functional disability levels equally between the 2 pathologies keeping in mind the difference in surgical indications as well as type of surgery performed.